The Influence of Assertiveness and Social Support from Families of Social Rehabilitation Program Participants on Islamic Communication Skills in Medan Class 1 Penitentiary - Nasution, Muhammad Yasir Halomoan; Madya, Efi Brata; Rubino, Rubino (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Social rehabilitation program, conveying religious messages and maintaining crucial aspects of religion and society. Effective communication is needed to build good relationships with other people, convey opinions and aspirations, and resolve conflicts with social rehabilitation program participants. This research aims to see the influence of assertive communication and social support from families of social rehabilitation participants on Islamic communication skills in the Class 1 Penitentiary in Medan. Based on the results of the research and discussion, several conclusions can be drawn as follows: First, assertiveness influences the Islamic communication skills of Social Rehabilitation Program Participants in Medan Class 1 Penitentiary. The results of this research identify that the better the level of assertiveness a person has, the Islamic communication skills of the inmates of class I Penitentiary in Medan will improve. Second, family social support influences the Islamic communication skills of Social Rehabilitation Program Participants in Medan Class 1 Penitentiary. The results of this research identify that the better the level of family social support received by a prison inmate will improve the Islamic communication skills of class I Medan Penitentiary inmates. Third, assertiveness and Social Support together have a significant effect on Islamic Communication Skills in Medan Class 1 Penitentiary, Participants in the Social Rehabilitation Program.